Relationships between patterns of cannabis use, abuse and dependence and recent stimulant use: Evidence from two national surveys in Ireland. - Seán R Millar (Public Library of Science (PLoS), 2021)
Background and objectives Epidemiological studies show that the use of cannabis is related to the use of other illicit drugs, including stimulants such as cocaine and ecstasy. However, few studies have examined how patterns of cannabis use relate to the use of stimulants. In this research we determined relationships between patterns of cannabis use and recent stimulant use, drawing on data from two large nationally representative surveys. We also explored how frequency of cannabis use relates to stimulant use and whether subjects with a cannabis use disorder (CUD)-defined as cannabis abuse or dependence-are more likely to be recent users of cocaine or ecstasy. Materials and methods We analysed data from Ireland's 2010/11 and 2014/15 National Drug Prevalence Surveys,which recruited 5,134 and 7,005 individuals respectively, aged 15 years and over, living in private households. We included only those people who reported some past cannabis use. Multivariable logistic regression analysis was used to examine associations between patterns of cannabis use and recent stimulant use. Results Among survey participants who had used cannabis in the last month, 17.9% reported recent cocaine use, while almost one-quarter (23.6%) reported recent ecstasy use. There was a significant linear relationship between patterns of cannabis use and recent use of cocaine, ecstasy or any stimulant, with last month cannabis users displaying greater odds (OR = 12.03, 95% CI: 8.15-17.78) of having recent stimulant use compared to last year (OR = 4.48, 95% CI: 2.91-6.91) and former (reference) cannabis users. Greater frequency of cannabis use in the last 30 days was also significantly related to the use of stimulants. In addition, results demonstrated an association between CUD and recent use of cocaine or ecstasy (OR = 2.28, 95% CI: 1.55-3.35). Conclusions Findings from this study suggest a relationship between patterns and frequency of cannabis use and recent use of stimulants and an association between CUD and stimulant use. As the use of cannabis with stimulants may increase the risk of negative health consequences, education in community and medical settings about polydrug use and its increased risks may be warranted.